Unsteady Free Convection Boundary Layer Flow at a Three-Dimensional Stagnation Point - Kumariand, M.; Nath, G. (Engineering Transactions, 1984)
The unsteady free convection flow at the stagnation point of a three-dimensional body under boundary layer approximations has been studied when the wall temperature varies arbitrarily with time. The semi-similar equations governing the flow have been solved numerically using an implicit finite-difference scheme. The heat transfer is found to be strongly dependent on time whereas the skin friction is weakly dependent on it. The increase in the Prandtl number results in the increase in heat transfer but skin friction is reduced. The mass transfer affects both the heat transfer and skin friction significantly, but for large times its effect on the heat transfer is very weak.